Hubungan Pola Asupan Zat Gizi dan Aktivitas Fisik dengan Status Gizi Penderita Hipertensi Prolanis Puskesmas Kotabumi II - Roza Mulyani; Adheya Rahma Putri; Bertalina Bertalina (Journal of Dietetics Science, 2026)
Lifestyle factors such as nutritional intake and physical activity often hinder successful blood pressure control.  This study aimed to provide a comprehensive overview of macronutrient intake, sodium, potassium, physical activity, and nutritional status of chronic disease management program members with hypertension in the working area of ​​Kotabumi II Health Center, North Lampung Regency in 2025. This was an observational analytical study with a cross-sectional approach involving 66 respondents at the Kotabumi II Public Health Center. Intake data were collected using the 24-hour food recall method, physical activity was measured using the Baecke Physical Activity Scale, and nutritional status was determined based on Body Mass Index (BMI). Bivariate data analysis was performed using the Chi-Square test and Pearson correlation. The majority of respondents were female (80.3%) and young-old adults (60–70 years). Most respondents had never received nutritional counseling (66.7%). Bivariate analysis showed a significant relationship between sodium intake (p=0.031), nutritional status (p=0.014), and physical activity (p=0.042) with blood pressure levels. The primary finding indicated that fat intake was the strongest determinant of BMI (p=0.002; r=0.747). There was an extreme nutritional imbalance characterized by high sodium intake (72.7%) and massive potassium deficiency (98.5%).  Nutritional status (obesity) and high fat intake are the dominant risk factors for hypertension among respondents.